DIRECT ORAL ANTICOAGULANTS ADJUSTMENT TO RENAL FUNCTION IN ATRIAL FIBRILLATION AND ATRIAL FLUTTER - Pereira, Mariana (2023)
Introduction: Atrial fibrillation and flutter are prevalent conditions. Direct oral anticoagulants require dose adjustment to glomerular filtration rate. The objective of this study was to assess the quality of prescription of direct oral anticoagulants in adults with these pathologies. Methods: We conducted an observational study in 5 Portuguese health care centers. We included adults with atrial fibrillation or flutter, a glomerular filtration rate under 50 mL/min, treated with direct oral anticoagulants and with updated weight and creatinine between june 2020 and may 2021. Glomerular filtration rate was calculated using Cockcroft-Gault formula and direct oral anticoagulants’ prescription adequacy was confirmed according to the summary of product characteristics. A descriptive analysis of the population was made. A correlation between prescription adequacy and patient characteristics, as well as the prescribed direct oral anticoagulant was assessed. Results: From 95 adults, 43 (45,3%) were male, with an average age of 83 years. 46 (48,4%) presented with inadequate anticoagulant prescription, from whom, 43 (45,3%) had an incorrect dosage and 3 (3,2%) had a formal contraindication to the treatment. We found no association between prescription adequacy, sociodemographic characteristics or the prescribed direct oral anticoagulant. Discussion: This study suggests that there is an important prevalence of inappropriate prescription of direct oral anticoagulant in patients with reduced glomerular filtration rate in primary health care, compromising the efficacy and safety of this medication. The glomerular filtration rate vigilance is necessary for a correct prescription of direct oral anticoagulants in patients with atrial fibrillation and flutter.